Land Procurement Policy For Development From the Perspective of Utilitarianism - Sannia Oktavienty (Locus Journal of Academic Literature Review, 2022)
Land issues become more crucial when population growth and increased development activities both by the government and by communities and individuals move on a relatively fixed land area, which simultaneously increases various land-use problems. The existence of various interests that seem to conflict with one another regarding land issues in development causes the process of land acquisition for development purposes to become a protracted problem. Therefore, it is necessary to review the policies that have been issued by the Government so far regarding land acquisition for infrastructure development, which is very closely related to the public interest based on a utilitarian perspective.